2018
DOI: 10.1186/s13100-018-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-LTR retrotransposons in the differentiation and evolution of anatomically modern humans

Abstract: BackgroundTransposable elements are biologically important components of eukaryote genomes. In particular, non-LTR retrotransposons (N-LTRrs) played a key role in shaping the human genome throughout evolution. In this study, we compared retrotransposon insertions differentially present in the genomes of Anatomically Modern Humans, Neanderthals, Denisovans and Chimpanzees, in order to assess the possible impact of retrotransposition in the differentiation of the human lineage.ResultsWe first identified species-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…However, the genomic architecture of L1 elements in ancient humans (Homo sapiens sapiens) and related subspecies, ancient hominids, (Neanderthals and Denisovans) are poorly understood due to the difficulties of genomic mapping of repeat elements using short reads available from the sequencing of ancient DNA. Nevertheless, several studies carried out an analysis of the mobile elements, which showed the presence of introgression of the L1 insertion loci of ancient people in the DNA of modern people, the nature of which corresponds to the same for SNV [98,99].…”
Section: Line Evolution In Ancient and Modern Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genomic architecture of L1 elements in ancient humans (Homo sapiens sapiens) and related subspecies, ancient hominids, (Neanderthals and Denisovans) are poorly understood due to the difficulties of genomic mapping of repeat elements using short reads available from the sequencing of ancient DNA. Nevertheless, several studies carried out an analysis of the mobile elements, which showed the presence of introgression of the L1 insertion loci of ancient people in the DNA of modern people, the nature of which corresponds to the same for SNV [98,99].…”
Section: Line Evolution In Ancient and Modern Humansmentioning
confidence: 99%
“…Thus, the origin of L1Ta1d could have occurred in the common ancestor of ancient hominids and modern humans more than 800 thousand years ago [98]. An analysis of the insertion loci in genes in ancient people and modern humans showed that most of the repeat insertion loci specific to modern humans, including L1, originated in the genes that are highly expressed in the brain and are involved in neuronal maturation [99].…”
Section: Line Evolution In Ancient and Modern Humansmentioning
confidence: 99%
“…The longest living bat species here considered are Myotis lucifugus and Myotis myotis (Figure 1). As seen above (Figure 3, Figure 5, Table 1), the non-LTR retrotransposons are the most present types of TEs in Rodents and the most extensively investigated by biomedical research given that they are the only active TEs in the human genome [11]. Since the TEs that may pose the highest health threat to organisms are the ones presently active, we compared the most recent accumulation of non-LTR retrotransposons between long-lived and cancer-resistant species (H. glaber) and short-lived species commonly affected by cancer (Figure 3, Figure 5) using the density of insertion (DI).…”
Section: Discussionmentioning
confidence: 92%
“…They can accumulate in genomes and account for most of the organism genome size, for example, the human genome is > 50% repetitive [3]. Many studies show that TEs are implicated in gene duplications, inversions, exon shuffling, gene expression regulation and may play an important role in the long-term evolution of organisms [4][5][6][7][8][9][10][11][12]. For example, the co-option of TE-related proteins gave rise to vertebrate acquired immune system and mammalian placenta [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that sites rich in repetitive sequences can be critical points for double-strand breaks, non-homologous recombination, and chromosomal reorganization in several organisms (Cazaux et al, 2011;Barros et al 2017;Cavalcante et al, 2018). Moreover, the high mobility of certain sequences (as transposable elements, or TEs) can enable them to interrupt the coding sequences of endogenous genes and modify their expression (Kemp and Longworth, 2015;Yin et al, 2018), or be co-opted for the regulation of host genes and thereby interfere with genome function and evolution (McCullers and Steiniger, 2017;Guichard et al, 2018).…”
Section: Introductionmentioning
confidence: 99%